Literature Review: Masalah Kesehatan Anak Jalanan - Az Zam zami, Akmal Haekal; Rossa, Elsye Maria (Poltekkes Kemenkes Tanjung Karang, 2021)
An increase in the number of street children saved by the world due to several factors such as family problems, poverty, difficulties in the household, parents, challenges, and family assistance are also reasons why children prefer to choose the road. This literature review aims to analyze or find out about health problems in street children. After reviewing the 5 articles, it can be concluded that three problems are often faced by street children, namely physical, psychological and social health problems. The problem of street children is a shared responsibility, the need for the role of cross-sectoral cooperation, both government, community, and educational institutions to solve the problems of street children.Â From this research, it is concluded that three problems are often faced by street children, namely physical, psychological and social health problems. Physical problems often experienced by street children are growth and nutrition problems, physical injuries, parasites and community-acquired infectious diseases, sexual and reproductive health problems, sexual violence and abuse, drug use and abuse. Meanwhile, the psychological problems of street children include psychiatric disorders such as depression, hopelessness, and suicidal thoughts. The social health problems of street children are economic and social. Street children are also often victims of neglect, psychological, physical, sexual abuse and are susceptible to sexually transmitted infections.Â